Seaweed biorefinery: A sustainable process for valorising the biomass of brown seaweed. (1st August 2020) - Baghel, Ravi S.; Suthar, Poornima; Gajaria, Tejal K.; Bhattacharya, Sourish; Anil, Annamma; Reddy, C.R.K.
Abstract: Marine macroalgal resources are gaining importance as one of the promising feedstocks for the production of food, feed, chemicals and energy which are upwardly growing worldwide. Recent studies have convincingly demonstrated the scope and potentials of seaweeds for the production of diverse bioproducts of commercial importance. The present study demonstrates an integrated strategy for sustainable utilisation of wet brown algal biomass ( Sargassum ) in laboratory-scale at 1 kg batch processing yielding 541.33 ± 5.50 mL sap, 32 ± 1.5 g alginic acid, 3.8 ± 0.2 g protein concentrate and 10 ± 0.5 g cellulose. Furthermore, the effluent obtained from the process was used to produce as much as 115 ± 5 g salt. The present integrated process has several advantages over contemporary ones in terms of reduction in input chemicals, and total utilisation of feedstock with effluent management. The green matrix analysis and economic assessment suggested that the commercial-scale implementation of the process could help to reduce the energy and chemical inputs for components extraction which are the major challenges with seaweed bioprocessing. Graphical abstract: Image 1 Highlights: High throughput and integrated process. High rate of biomass utilisation (93%) is the hallmark of this process. Process integrated with effluent management. Reduction in consumption input chemicals. Densification of product in successive process as it progresses.